Unraveling the Essential Role of Consecutive Protonation Steps in Photocatalytic CO2 Reduction when Using Au Nanorods in a MOF - Huang, Tianyi; Han, Jianyu; Li, Zhongqiu; Hong, Yixin; Gu, Xiaofei; Wu, Yafeng; Zhang, Yuanjian; Liu, Songqin (Angewandte Chemie International Edition, 2025)
The proton‐coupled electron transfer process (PCET) plays a crucial role in both natural and artificial photosynthesis, including CO2 fixation chemistry. However, difficulties in capturing the transient intermediates generated during the protonation process impede the clarification of the fundamental mechanism behind photocatalytic CO2 reduction. Herein, we report a general killing two birds with one stone strategy by spatially confining Au nanorods within a typical porphyrin metal–organic framework (MOF). Interestingly, 2.4‐fold increase in CH4/CO selectivity and 12‐fold increase in CH4 production were observed after loading of Au nanorods, indicative of a strengthened protonation process in the photocatalytic CO2 reduction. More importantly, the plasmonic effect from Au nanorods simultaneously boosted the in situ Raman signals of *CO and *CHO intermediates on the Au−O−Zr active site. The evident protonation process was further clarified in a control H/D kinetic isotope experiment. This work highlights the significance of successive protonation steps for boosting CH4 production in photocatalytic CO2 reduction. The integration of Au nanorods not only improves the selectivity and production rate of the photocatalytic CO2 reduction but also provides crucial insights into the pivotal role of protonation steps and reaction intermediates, particularly highlighting the rate‐determining *CO to *CHO conversion.